2021
DOI: 10.1017/s1047951121002833
|View full text |Cite
|
Sign up to set email alerts
|

Feeding outcomes in post-discharge feeding clinic for infants following cardiac surgery

Abstract: Introduction: The aim of this study was to describe the development and assess the usefulness of a feeding clinic to help infants with CHD tolerate the highest level of oral feeding while achieving growth velocity and supporting neurodevelopment. Materials and methods: This retrospective, cohort study assessed feeding outcomes for infants who underwent cardiac surgery at <30 days of age with cardiopulmonary bypass between February 2016 and April 2020. Diagnoses, age at surgery, hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…These problems are commonly researched in the cardiac population, since fatigue is a frequent cause of feeding disruption for these infants (Jones et al, 2021). One study found that post cardiac surgery the most common problems included fatigue, poor tone, weakness, need for respiratory support and pain (Jones et al, 2022). Another study instigated a program involving speech and language therapists, occupational therapists, physiotherapists, nurses and lactation consultants to develop teaching to support nursing staff to identify when infants require altered feeding practices due to physiological instability.…”
Section: Difficulties Directly Related To the Child's Conditionmentioning
confidence: 99%
“…These problems are commonly researched in the cardiac population, since fatigue is a frequent cause of feeding disruption for these infants (Jones et al, 2021). One study found that post cardiac surgery the most common problems included fatigue, poor tone, weakness, need for respiratory support and pain (Jones et al, 2022). Another study instigated a program involving speech and language therapists, occupational therapists, physiotherapists, nurses and lactation consultants to develop teaching to support nursing staff to identify when infants require altered feeding practices due to physiological instability.…”
Section: Difficulties Directly Related To the Child's Conditionmentioning
confidence: 99%